Logic Model Analysis of Bituo Innovation Program in Cashless Transactions for Local Government Revenues Management in Boalemo Regency, Indonesia - Muhammad, Ikram; Sukrianto; Wahdah, Ghoriqna F (Westscience Press, 2025)
Innovation is an effort to reform the management and administration of local government affairs. Bituo is an innovation in public financial sector of tax and retribution cashless payment in Boalemo Regency Government. This research aims to analyze the Bituo innovation program in managing cashless transactions using a logic model which limited to the dimensions of input, activities and output of innovation program. The research results show that the Bituo program is a form of top-down innovation in the public financial sector due to regulatory direction, the political will of local leaders, government resources supported, private sector partnership, and people literacy. Electronification of local tax and retribution payments made public financial management is more effective, efficient, and reduces the fund leaks potential.